2012
DOI: 10.1177/1040638712445763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HistoGel™-embedded specimens for use in veterinary diagnostic pathology

Abstract: HistoGel™ is an aqueous specimen-processing gel that encapsulates and suspends histologic and cytologic specimens in a solidified medium. HistoGel-embedded specimens can then be processed and evaluated by routine histologic and immunohistochemical methods. This methodology has been used in human diagnostic pathology and is especially useful for small, friable, or viscous tissue samples that are difficult to process. In addition, special histochemical stains or immunohistochemistry can be performed on HistoGel-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…After resuspension in HistoGel (RichardAllan Scientific, Kalamazoo, MI), such cell pellets can then be fixed in 10% NBF and routinely processed for histopathology, IHC, and ISH like any other tissue sample. 53 …”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…After resuspension in HistoGel (RichardAllan Scientific, Kalamazoo, MI), such cell pellets can then be fixed in 10% NBF and routinely processed for histopathology, IHC, and ISH like any other tissue sample. 53 …”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…Histogel preparations were made as previously described . Briefly, the solidified Histogel (Richard‐Allan Scientific, Kalamazoo, MI, USA) was melted by placing the tube of Histogel in a water bath and heating to 55‐65°C.…”
Section: Methodsmentioning
confidence: 99%
“…Cell block preparation techniques that can be performed by veterinarians in‐house could be useful in limiting the effects of storage and temperature on cell morphology and could also limit the need for a cytocentrifuge. Histogel is an aqueous gel that allows suspension of tissue and fluid samples in a solidified medium . These specimens are then formalin‐fixed, processed, and evaluated by routine histologic and immunohistochemical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed advantages of the CB as documented in human studies include: (a) the preservation of tissue architecture, (b) sample archivability owing to paraffin embedding, (c) the suitability of samples for cytochemical and immunohistochemical staining, (d) a reduced need for excisional biopsy and (e) advantages in the detection of certain malignancies, including lymphoma . Limited studies on the CB or CB‐like techniques in veterinary medicine have demonstrated its utility in the evaluation of lymphoid tissues and in the detection of fungal osteomyelitis, leishmaniasis, mesothelioma and bone marrow carcinoma micrometastasis . While all veterinary publications describing the CB testify to its ease of use, only one has evaluated its utility in the evaluation of the canine reactive and lymphomatous lymph node and in the diagnosis of lymphoma.…”
Section: Introductionmentioning
confidence: 99%